2023
DOI: 10.3390/ijerph20032405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Housing Deprivation on Health: Empirical Evidence from Spain

Abstract: Severe housing deprivation rates in Spain have tripled in just four years, affecting 3.4% of the population in 2020, with a higher incidence among the low-income population (9.2%). Despite the social aspect of the problem, minimal research has been carried out in Spain on the effects that the various forms of housing deprivation have on health. This study analyzes the impact of housing deprivation on health outcomes, with the objective of achieving results that facilitate the creation of improved public polici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…A study from Spain concludes that elements of housing that result in the greatest adverse effect on general health are noise, leaks, and harmful temperatures. Survey respondents also complain about pollution, neighborhood crime, and population density [36].…”
Section: The Role Of Housing and Homelessnessmentioning
confidence: 99%
“…A study from Spain concludes that elements of housing that result in the greatest adverse effect on general health are noise, leaks, and harmful temperatures. Survey respondents also complain about pollution, neighborhood crime, and population density [36].…”
Section: The Role Of Housing and Homelessnessmentioning
confidence: 99%
“…Based on Malsow's pyramid of needs, it can be concluded that housing, apart from being classified as a basic need (located at the bottom of the pyramid), also enables the higher-level needs to be met (Kozera & Kozera, 2014), such as the need for security, belonging, recognition or self-fulfillment. In addition to providing the basis for meeting living needs, housing is one of the basic material elements (Dziechciarz-Duda, 2017) enabling the enjoyment of other human rights, such as education and health (Tyrell & Tuppett, 2017;Carmona-Derqui, 2023). Housing conditions, including the physical and structural characteristics of housing, are important components of the broadly understood concept of quality of life (Marsch et al, 2000;Braubach & Fairburn, 2010;Rasnaca, 2017;Tyrell & Tuppett, 2017;Sikora-Fernadez, 2018;Ibrahim, 2020;Zumaya & Motlak, 2021;Matel & Marcinkiewicz, 2021;Ulman & Ćwiek, 2021).…”
Section: Introductionmentioning
confidence: 99%